The Effectiveness of Cooperative Model CIRC Type Assisted by Schoology on The Mathematical Literacy Ability of Junior High School Students (Journal of Primary Education, 2019)
The purpose of this study was to determine the effectiveness of cooperative model CIRC type assisted by Schoology on the mathematical literacy ability. Schoology in this research is a free web-based education application which allows teachers to give lessons to students digitally. This study method applied in this research was a quantitative method of quasi-experimental with Nonequivalent Control Group Design model. The population of this study was the grade VII students of Public Junior High School 5 Kudus. Sampling was done by using simple random sampling. Data collection technique was used mathematical literacy ability tests, observation, and documentation, respectively. This study was analyzed using t-test. The results show that the mathematical literacy ability using the cooperative model CIRC type assisted by Schoology has reached 75% of classical completeness, the average mathematical literacy ability using the cooperative model CIRC type assisted by Schoology was better than the average mathematical literacy ability using the expository learning model, the proportion of students 'mathematical literacy ability using the cooperative learning model CIRC type assisted by Schoology was more than the proportion of students' mathematical literacy ability using the expository learning model. The average of total teaching skills and activities of students in mathematics learning was in very good criteria.